Effects of pension eligibility expansion on men’s memory decline and dementia probability: Findings from the HAALSI cohort in rural South Africa, 2014–2021 - Janet Jock; Erika T. Beidelman; Meredith Phillips; Lindsay C. Kobayashi; Xiwei Chen; Stephen Tollman; Chodziwadziwa Whiteson Kabudula; Darina T. Bassil; Ryan Wagner; Lisa Berkman; Molly Rosenberg (PLoS ONE, 2025)
Alzheimer’s disease and related dementias (ADRD) are a growing global health concern, with burdens projected to expand rapidly in the coming decades. Since cognitive decline typically precedes ADRD, it is crucial to identify interventions that may help slow cognitive decline and reduce ADRD risk. We used a quasi-experimental design, exploiting exogenous expansions of South Africa’s Older Persons Grant for men, to estimate its impact on memory decline and ADRD risk in the rural Mpumalanga province of South Africa. We found that expanded pension eligibility was associated with slower memory decline for men who were eligible to receive the pension 5 years earlier [β = 0.027 SD, 95% CI = 0.023, 0.031], as well as for men who were eligible to receive the pension 1−4 years earlier [β = 0.009 SD, 95% CI = 0.004, 0.013]. We also found a 5.2 percentage point lower probability of dementia for men who were eligible for pension 5 years earlier [95% CI = −0.062, −0.032] and a 4.8 percentage point lower probability of dementia for men who became eligible to receive pension 1−4 years earlier [95% CI = −0.062, −0.032]. These findings demonstrate that beyond the policy intent of cash transfers to strengthen individual and household livelihoods, an important further benefit lies in promoting healthy cognitive aging in low- and middle- income countries.